Construction of Tourism Supply Chains Based on Consumer and Service Provider Responses - Hadházi, Viktória (International Journal of Engineering and Management Sciences, 2022)
The tour operator wants to satisfy all the needs of those who want to travel at the highest possible level. Experiences related to planning and organizing trips are almost as important as the vacation or excursion itself. My study compares the characteristics of domestic and foreign trips based on the consumers responses. The comparison was done by the following points: time for preparations, the reservation process, getting to the selected destination, the hotel selection, or the duration of the journey. At the same time, the chain is completed with tourism service providers, whose cooperation is key to meet the needs of travellers, all in the common interest of the guest being satisfied when they return home.